Negative Pressure Wound Therapy in Orthopedic Surgery (Review) - Zazirnyi, I.M.; Kravchenko, D.D.; Andreev, A. (TERRA ORTHOPAEDICA, 2020)
Summary. Negative pressure wound therapy (NPWT), in its most used Vacuum Assisted Closure (VAC) variant, consists in applying subatmospheric pressure to a wound that is sealed off by a specially designed dressing and connected by a tube to a suction pump and drainage collection system. Skin defects are extremely common in orthopedic and trauma surgery. VAC is valuable across a range of indications. Proven effects include an increase in blood flow, stimulation of angiogenesis, and a decrease in wound surface area. VAC can be used to treat post-traumatic and surgical wounds, burns, and chronic wounds such as pressure sores and ulcers. The lower frequency of dressing changes with VAC lightens the staff workload. The public health services of Australia, Belgium, Canada, New Zealand, the United States, Germany, and France have issued good practice guidelines for the use of VAC in specific and limited indications. VAC has benefited from the introduction of several technological improvements such as silicone interfaces, foam dressings with various densities and pore sizes, and irrigation systems. The result of using this method is greater adaptability to each specific situation. Nevertheless, VAC is not appropriate in every case and cannot replace a necessary surgical procedure. The aim of this study is to review the principles, practical modalities, and indications of VAC.